Beneficial effects of secretory leukocyte protease inhibitor after spinal cord injury - Ghasemlou, Nader (Oxford University Press, 2010)
Secretory leukocyte protease inhibitor is a serine protease inhibitor produced by various cell types, including neutrophils and activated macrophages, and has anti-inflammatory properties. It has been shown to promote wound healing in the skin and other non-neural tissues, however, its role in central nervous system injury was not known. We now report a beneficial role for secretory leukocyte protease inhibitor after spinal cord injury. After spinal cord contusion injury in mice, secretory leukocyte protease inhibitor is expressed primarily by astrocytes and neutrophils but not macrophages. We show, using transgenic mice over-expressing secretory leukocyte protease inhibitor, that this molecule has an early protective effect after spinal cord contusion injury. Furthermore, wild-type mice treated for the first week after spinal cord contusion injury with recombinant secretory leukocyte protease inhibitor exhibit sustained improvement in locomotor control and reduced secondary tissue damage. Recombinant secretory leukocyte protease inhibitor injected intraperitoneally localizes to the nucleus of circulating leukocytes, is detected in the injured spinal cord, reduces activation of nuclear factor-κB and expression of tumour necrosis factor-α. Administration of recombinant secretory leukocyte protease inhibitor might therefore be useful for the treatment of acute spinal cord injury.